Yield and Profitability of New Wheat Varieties in Madhya Pradesh (Indian Journal of Extension Education, 2010)
High yielding and good quality wheat varieties of the Central Zone were tested in farmers’ field to know about productivity and profitability. Wheat frontline demonstrations were conducted by a team of scientists at chosen locations in farmers’ fields in various districts of Madhya Pradesh viz. Jhabua, Dewas, Indore, Dhar, Shajapur, Vidisha and Khargone between 2001-02 to 2005-06 using breeder seed. Farmers used own other inputs including machinery, and raised the crop according to recommended technology. They tried to implement these technologies to their maximum according to their resources. Wheat crop raised by farmer in the nearby field on their own was considered as check. Popular varieties like Lok1, WH 147 and Sujata (HI 617) were considered as checks in different demonstrations. On the basis of gross return per rupee invested durum wheat variety HI8627 (Malavkirti) gave best returns (1 : 4) to the farmers followed by (1 : 3.9) aestivum variety HI 1531 (Harshita). Higher yields and better quality earned higher market price leading to better profits in test varieties as compared to checks in all the cases. Higher yields and better quality led to better profits in test varieties as compared to check varieties in both the categories. Cost of cultivation was higher in test varieties due to recommendation of manual labour for weeding and other intercultural operations.